Union of the Comoros : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper analyzes the decentralization of government in the Union of the Comoros and its economic management functions foreseen under the constitution. The paper examines the special challenge of combining a civil service reform needed to increase the efficiency of the civil service with the decentralization of the civil service foreseen under the new constitution. It discusses developments in a number of civil service indicators that are often used to analyze the government wage bill and employment in relation to economic and fiscal objectives.